LGBTQI' Defined: An Introduction to Understanding and Caring for the Queer Community - Joseph Gallego; John Knudsen (Association of American Medical Colleges, 2015)
Abstract Introduction LGBTQI' Defined: An Introduction to Understanding and Caring for the Queer Community was designed to improve the quality of care provided to the LGBTQI' community by educating health care professionals about the complexities of queer culture. The curriculum uniquely and interactively deconstructs sex, gender, and sexual orientation as separately experienced entities comprising an individual's identity. This innovative approach to teaching a challenging topic allows learners to discover a deeper understanding of their own identities while developing greater empathy for LGBTQI'-identified people. Additionally, the curriculum defines other terminology and identities relevant to the LGBTQI' population. Finally, "LGBTQI' Defined" provides learners with institutional considerations and specific clinical recommendations and techniques to help providers care for their future LGBTQI'-identified patients with compassion and cultural sensitivity. Methods The module includes PowerPoint presentations, activity guides, and evaluations. Positive evaluations have been collected from the presentations given at Mayo Clinic. Results Of the learners who have completed evaluations, 99% (n = 110) rated the overall value (relevance to their professions) of the curriculum as "very good" or "excellent," and 98% (n = 87) rated the overall quality (effectiveness of curriculum) as "very good" or "excellent." Ninety-nine percent (n = 92) "agreed" or "strongly agreed" that the five learning objectives were successfully met. Discussion Specific learner feedback supports the interactive and didactic elements of the curriculum and the importance of delivering LGBTQI healthcare-related education to providers.